Clinical presentation, microbiology, and prognostic factors of prosthetic valve endocarditis. Lessons learned from a large prospective registry. - Antonio Ramos-Martínez; Fernando Domínguez; Patricia Muñoz; Mercedes Marín; Álvaro Pedraz; Mª Carmen Fariñas; Valentín Tascón; Arístides de Alarcón; Raquel Rodríguez-García; José María Miró; Josune Goikoetxea; Guillermo Ojeda-Burgos; et al. (PLoS ONE, 2023)
Background Prosthetic valve endocarditis (PVE) is a serious infection associated with high mortality that often requires surgical treatment. Methods Study on clinical characteristics and prognosis of a large contemporary prospective cohort of prosthetic valve endocarditis (PVE) that included patients diagnosed between January 2008 and December 2020. Univariate and multivariate analysis of factors associated with in-hospital mortality was performed. Results The study included 1354 cases of PVE. The median age was 71 years with an interquartile range of 62-77 years and 66.9% of the cases were male. Patients diagnosed during the first year after valve implantation (early onset) were characterized by a higher proportion of cases due to coagulase-negative staphylococci and Candida and more perivalvular complications than patients detected after the first year (late onset). In-hospital mortality of PVE in this series was 32.6%; specifically, it was 35.4% in the period 2008-2013 and 29.9% in 2014-2020 (p = 0.031). Variables associated with in-hospital mortality were: Age-adjusted Charlson comorbidity index (OR: 1.15, 95% CI: 1.08-1.23), intracardiac abscess (OR:1.78, 95% CI:1.30-2.44), acute heart failure related to PVE (OR: 3. 11, 95% CI: 2.31-4.19), acute renal failure (OR: 3.11, 95% CI:1.14-2.09), septic shock (OR: 5.56, 95% CI:3.55-8.71), persistent bacteremia (OR: 1.85, 95% CI: 1.21-2.83) and surgery indicated but not performed (OR: 2.08, 95% CI: 1.49-2.89). In-hospital mortality in patients with surgical indication according to guidelines was 31.3% in operated patients and 51.3% in non-operated patients (p<0.001). In the latter group, there were more cases of advanced age, comorbidity, hospital acquired PVE, PVE due to Staphylococcus aureus, septic shock, and stroke. Conclusions Not performing cardiac surgery in patients with PVE and surgical indication, according to guidelines, has a significant negative effect on in-hospital mortality. Strategies to better discriminate patients who can benefit most from surgery would be desirable.